Characterization of Maltodextrin DP 3-9 and Assesment of Its Potential Application as Carbohydrate Source in Sport Drink - Beni Hidayat; Adil Basuki Ahza; Sugiyono . (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2003)
This research was aimed at characterization of maltodextrin DP 3-9 (produced by enzymatic hydrolysis and membrane separation process) as compared to commercial maltodextrin and glucose and assessment of its potential application as carbohydrate source in sport drink. The research showed that application of maltodextrin DP 3-9 had some advantages as compared to glucose with regard to absorption rate that was 2 times longer (60 minutes instead of 30 minutes), osmolality degree that was 5,6 times lower (178 mOsmol/kg as compared to 1000 mOsmol/kg), and relative sweetness degree that was 10 - 11 times lower (6,15-7,20 as compared to 57,00-61,00). However, thie application of maltodekstrin DP 3-9 had limitation which was shown by its viscosity characteristic that was 5,70 – 6,20% higher (1,29 cSt and 1,37 cSt as compared to 1,22 cSt and 1,29 cSt). When compared to commercial maltodextrin, maltodextrin DP 3-9 is favorable as carbohydrate source in sport drink based on its absorption rate that was more than 2 times faster (60 minutes as compared to more than 120 minutes) and storage stability at refrigeration temperature (which was more than 8 weeks, with or without sterilization; with sterilization). Key words : Maltodextrin DP 3-9, carbohydrate source and sport drink